Is laparoscopic major hepatectomy feasible and safe in Swiss cantonal hospitals? (Swiss Medical Weekly, 2021)
BACKGROUND: The number of laparoscopic liver resections is increasing worldwide, including in Switzerland. However, laparoscopy is mostly used for minor resections. Little is known about indications for and outcomes of major liver resections performed laparoscopically. The aim of this study was to compare the clinical outcome of open and laparoscopic major liver resection cohorts in two Swiss centres.METHODS: Patients undergoing open or laparoscopic major hepatectomy (>3 segments) in two cantonal hospitals from January 2015 to December 2019 were analysed. All disease types except perihilar cholangiocarcinomas, rare malignancies and resections with biliary reconstruction were included. The primary outcome was the number of complications incurred. Operation time, blood loss, hospital stay and 90-day mortality were secondary outcomes investigated. A separate analysis was performed for colorectal liver metastases, the most common indication. Potential risk factors for major complications were evaluated in a multivariate analysis.RESULTS: A total of 88 patients were identified. Among those, 34 patients underwent laparoscopic major hepatectomy (LAPH) and 54 patients open major hepatectomy (OH). The two groups did not differ in demographics. The most common indication was malignancy (LAPH 94% vs OH 98%), mainly colorectal liver metastases (LAPH 53% vs OH 59%). There was no significant difference in major complications (21% vs 15%, p = 0.565). Median operation time (LAPH 433 minutes, interquartile range [IQR 351–482  vs OH 397 minutes, IQR 296–446; p = 0.222), blood loss (325 ml, IQR 200–575 vs 475 ml, IQR 300–800; p = 0.150) and hospital stay (9 days, IQR 8–14 vs 11 days, IQR 9–14; p = 0.441) were comparable between the two cohorts. There was no significant difference in 90-day mortality (3% vs 7%, p = 0.881). The laparoscopic technique was not identified as a risk factor for major complications in a multivariate analysis.CONCLUSION: This first report from Switzerland evaluating outcomes of laparoscopic major hepatectomies showed no difference in complications and clinical non-inferiority compared with open major hepatectomy.